Manajemen Sanggar Seni Lakon Gerak Minang Di Nagari Baringin Kabupaten Tanah Datar - Sri Indah Suci Amalia; Afifah Asriati (SENDRATASIK UNP, 2021)
The Management of Lakon Gerak Minang Art Studio in Baringin Village, Tanah Datar Regency. A Bachelor Thesis. Sendratasik Department. FBS. Universitas Negeri Padang. This research aims to describe and explain the management system of Lakon Gerak Minang Art Studio in Baringin Village, Tanah Datar Regency. This research belongs to a qualitative research using descriptive method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing tools and cameras. The data types used in this study were primary and secondary data. The data were collected through literature studies, observations, data analysis, and data collection. The results show that Lakon Gerak Minang art studio has a management consisting of managing, planning programs, and dividing various activities, tasks and responsibilities. Organizational processes are interconnected with each other. If one process is not executed properly, the other processes will not well. Therefore, every process must be done properly so that the studio management system can run well. Thus, it makes Lakon Gerak Minang art studio able to compete with other studios in Tanah Data Regency. The management system run by Lakon Gerak Minang art studio belongs to the line organization (a form of organization where the delegation of authority is directly vertical and entirely given from the leader to the subordinates). The advantage of this line organization is that all decisions can be resolved directly because in a certain situation the leader becomes one of the main targets in solving problems. The weakness of this organization is the problems cannot be resolved quickly due to the fact that the leader is not there. Thus, the management of this organization is to solve problems which exist in the studio.The head of the studio becomes the first person to complete and resolve the problems.